What Helps Primary School Teachers at the Beginning of their Career to Facilitate the Inclusion of Pupils with Special Educational Needs and Disabilities: A Q-Methodology Study. - Butler, Jessica (2024)
Inclusion continues to be an important goal for all children attending schools in England. Whilst this is stated in the Special Educational Needs and Disability (SEND) code of practice, there is a lack of clarity regarding how to facilitate inclusive classrooms. Teachers are key facilitators of inclusion, and this incorporates primary school teachers at the beginning of their career. Addressing a key gap in the literature, this study explores the views of fourteen primary school teachers (in their first, second and beginning of third year of teaching) regarding what helps them to facilitate the inclusion of pupils with SEND in mainstream schools. Using Q-methodology, this study brings together the advantages of quantitative and qualitative approaches, to clarify participants holistic and subjective views and promote open communication around a complex topic. Participants completed a 32 statement Q-sort, arranging possible answers to the question “what helps you to facilitate the inclusion of pupils with SEND in your classroom” on a continuum from more helpful to less helpful. Findings show that most statements (24 out of 32) were considered helpful. By-person factor analysis revealed three distinguishable viewpoints and highlight the importance of the following areas: • Viewpoint 1: Relationships and collaboration with pupils, parents, and staff. • Viewpoint 2: Experience, advice, and training. • Viewpoint 3: Teacher-pupil relationships, experience, and independent learning. Results suggest that a singular approach toward inclusion may not be appropriate, with a range of areas considered helpful for participants. However, areas of consensus show that teacher-pupil relationships and support from the SEND coordinator were helpful for all 3 viewpoints. This study develops our understanding of what helps primary school teachers at the beginning of their career to facilitate inclusion – providing ways forward for future research and individuals with a desire to promote inclusive practice.